Does Immigration Undermine Public Support for Integration in the European Union?1. (13th January 2015) - Toshkov, Dimiter; Kortenska, Elitsa
Abstract It is well established that negative attitudes towards immigrants are strongly associated with lower public support for European integration. But the impact of actual immigration levels on immigration attitudes is still contested. As a result, the relationship between immigration levels and EU public support remains uncertain from a theoretical point of view. We offer an empirical study of the link between immigration from the new EU member states from Central and Eastern Europe (CEE) and EU support at the regional level in Spain, France, Ireland and The Netherlands. The results of the analyses suggest that in all four countries immigration from CEE had negative effects on support for European integration in the host societies. In short, immigration seems to undermine integration, although internal migration within the EU is necessary for the successful functioning of its economic union and the future of political integration.